New species and records of Apseudomorpha (Crustacea: Tanaidacea) from Taiwan - Tzeng, You-Wei; Hsueh, Pan-Wen (Zootaxa, 2014)
The present study reports the first record of Apseudomorpha from Taiwan and includes descriptions of three new species and one new species record. Paradoxapseudes pangcahi sp. nov. differs from the most similar congener, Paradoxapseudes littoralis, by having one segment less in the antennal flagellum and fewer segments in the uropod endopod. Pseudoapseudomorpha tagopilosus sp. nov. is distinguished from its most similar congener, Pseudoapseudomorpha ornata, by having one long lateral seta on pleonite 4, a four-segmented antennular outer flagellum, and a male with smaller and thinner ‘small’ cheliped than that of the female and with vestigial pleopods on pleonite 3. Indoapseudes multituberculata sp. nov. stands out from its congeners by having pleopods only on the last two pleonites in females, many small tubercles terminally on the pleotelson, and mandibular palp article 1 with noticeable distal teeth. The Synapseudes species recorded in the present study morphologically agrees with Synapseudes hansmuelleri that was originally described from the Tioman Archipelago, Malaysia, South China Sea. Morphological comparisons between each of the three newly described species and its congeners are tabulated.